Anatomic variations of posterior paranasal sinuses and optic nerve - Alma Efendić; Edin Muharemović; Rasim Skomorac; Hakija Bečulić; Sabina Šestić; Benjamin Halilović; Mersiha Mahmić-Kaknjo (Medicinski glasnik, 2017)
Aim: To define direct anatomical relations of the sphenoidal (alae minores), ethmoidal sinuses and optic nerve, with an emphasis on determining the effect of age on pneumatisation and dehiscence. Methods: This retrospective, descriptive study involved 60 consecutive patients: 30 patients younger than 30 and30 patients older than 60 years of age. All patients underwent computerized tomography (CT). The relationship of the optic nerve and the sphenoidal and ethmoidal sinuses was classified. The presence of dehiscence in the bone structures, forming the optic canal, was checked. Dehiscence was defined as absence of visible bone density located between the sinus and the optic nerve. Protrusion of the optic nerve into the sphenoidal sinus was defined as optic nerve surrounded by pneumatised space. Results: The most common type of relation between the optic nerve and sphenoidal sinus was type I, where the optic nerve was immediately adjacent to the lateral or superior wall of the sphenoidal sinus, without impression on the sinus wall. Dehiscence was documented in 15 (25%) cases, it was more common in older patients (8, 27%) than in younger ones (7, 23%). The pneumatisation processes were more frequent in patients over 60 (5, 17%) than in those younger than 30 years (4, 13%). Conclusion: Surgeons and ophthalmologists should be aware of high frequency of dehiscence of sphenoidal sinus walls when treating adult patients in our population, especially when evaluating risks and complications of surgical procedures or when diagnosing inflammatory or tumorous processes in the close vicinity of posterior paranasal sinuses.
Keywords: ethmoid sinus; sphenoid sinus; intraoperative complications